Implikasi Profesi Pramugari Terhadap Rumah Tangga - , Nanik Rianandita Sari, S.S, Prof. Dr. Kodiran,M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Working women is a usual thing in Indonesian, the purpose of women working is helping family financial. Various kind of jobs can be done by women, one of it is a flight attendant, this is favorite profession by many woman, because it does not need high education to apply this jobs but it is need skills and disciplines because flight attendant works for services and flight attendant has big duty and role. Flight attendant who has married and has child, they should be able to manage their time between job and family. Women as a wife has to be active in manage house hold and help family financial. So, that flight attendant share the house hold with husband. Every decision about taking care of child, managing house hold are discussed with husband so the house hold can be handled. Based on that, statement problem in this research are: what makes married woman still working as a flight attendant?